2009
DOI: 10.1097/fpc.0b013e32832c347d
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution HLA genotyping and severe cutaneous adverse reactions in lamotrigine-treated patients

Abstract: No single major HLA-related genetic risk factor was identified for lamotrigine-induced SCARs in patients of European origin. Only suggestive evidence was obtained for B*5801, A*6801, Cw*0718, DQB1*0609, and DRB1*1301. Confirmation of these results in a larger, independent sample is needed to determine whether any of the HLA alleles identified are truly associated with the development of lamotrigine-induced SCARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 17 publications
0
52
1
Order By: Relevance
“…49,50,82 No association was found between LTG-SJS/TEN and HLA-B*1502 in Chinese, 68 or European patients. 58 In our study, we observed that negative HLA-B*1502 does not predict negative LTG-HSR. We conclude that HLA-B*1502-negative status is not protective against LTG-HSR.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…49,50,82 No association was found between LTG-SJS/TEN and HLA-B*1502 in Chinese, 68 or European patients. 58 In our study, we observed that negative HLA-B*1502 does not predict negative LTG-HSR. We conclude that HLA-B*1502-negative status is not protective against LTG-HSR.…”
Section: Discussionmentioning
confidence: 47%
“…53 The parental drug was added at its therapeutic concentration. 53 The HLA polymorphism was determined using the method described by Kazeem et al 58 Enzyme-linked immunosorbent assay (ELISA) immunoassay kits for human IL-1, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, MCP1, regulated upon activation normal T-cell expressed and secreted (RANTES) and TNF-α (e-Bioscience, San Diego, CA, USA), as well as Fas, cleaved caspase 8, M30-Apoptosense ELISA (Bender MedSystems, Vienna, Austria) were used for quantitative determination. We used standards and reference reagents available from Bender MedSystems (Vienna, Austria).…”
Section: Preparation Of the Ltamentioning
confidence: 99%
“…25 Associations were tested using two tails permuted (100 000 times) Fisher's exact analysis using PLINK software, by considering duplications and deletions separately. 16 We also investigated singleton CNVs 4100 kb 26 to find evidence for individual predisposition to SJS/TEN. For this analysis, we adopted a coverage cutoff excluding all CNVs that had coverage 420 genetic markers/CNVs.…”
Section: Cnv Analysismentioning
confidence: 99%
“…Cases were defined by Kazeem et al 16 All cases and controls were epilepsy patients treated with lamotrigine and recruited retrospectively. Cases were patients who developed SJS/TEN or hypersensitivity reactions (although only SJS/TEN cases are included in this study), whereas controls were patients exposed to lamotrigine without developing SJS/TEN.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation